A Theory of Political Backlash: Assessing the Religious Right's Effects on the Religious Field. (15th November 2021) - Braunstein, Ruth
Abstract: A growing body of evidence suggests that the rise in religious disaffiliation can be partly attributed to a political backlash against the Religious Right. Yet the concept of "political backlash" remains undertheorized, limiting our ability to evaluate how backlash against the Religious Right has impacted the religious field as a whole. This article develops a general account of how political backlash against a radical actor can impact participants within a given field, distinguishing between broad backlash, narrow backlash, and counter backlash . It then applies this framework to the case of the religious field. An analysis of available evidence suggests that backlash against the Religious Right has had ripple effects beyond the rise of the "nones, " including a rise in "spiritual" identification, positive attention to the "Religious Left, " depoliticization of liberal religion, and purification and radicalization within the Religious Right itself. This article encourages religion scholars to connect dots between trends that have not been understood as related, and deepens our understanding of the relational nature of religious change. More generally, it offers a framework for understanding how backlash against radical actors can shape entire fields.